Jangha of the Garbhagriha of the Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The exterior wall of the garbhagriha (sanctum sanctorum) of the Hazareshwar Temple presents a blend of bhadras (central projections) and stambhas (pillars), creating a captivating visual tapestry. The bhadras, intricately carved on the cardinal directions, serve as focal points of the structure’s architectural elegance, while the stambhas fill the spaces in between.